Let’s Kahoot! A game-based technology for creating engagement and promoting active learning - Hilmun, Perisya; Fitriah, Fitriah (Universitas Islam Negeri Raden Intan Lampung, 2021)
Nowadays, the development of technology plays an essential role in many aspects of human life. People activity cannot be separated with the assistance of technology, including in education. Teachers often utilise technology to transform the information, make students motivated and engaged, and assess the progress of the learnt materials. Among the available technological tools, Kahoot is a digital game application that can be integrated into teaching. Teachers could use this application to promote active learning. This research aimed to explore the use of Kahoot in teaching as to increase students’ engagement and encourage active learning. The study reviewed 18 published research papers identifying teachers’ approaches in integrating Kahoot in their practices, the function and the effect of Kahoot in classroom environment within the context of EFL teaching. The result of review papers indicated that teachers utilised Kahoot to review and practice the learnt materials, and they used Kahoot at different times. All studies showed that the implementation of Kahoot could create a positive learning environment allowing students to participate actively. This study implies that teachers can integrate any digital game application into their teaching practices to make students engaged and promote active learning. However, teachers need to understand how to use the application correctly and identify whether the choice application is suitable for the students’ level and needs.